The Role of E-Procurement in the Austrian Construction Industry: Adoption Rate, Benefits and Barriers - Markus Zunk, Bernd; Johannes Marchner, Martin; Uitz, Iris; Lerch, Carina; Schiele, Holger (International Journal of Industrial Engineering and Management, 2014)
The progressive developments force suppliers on efficiency-driven construction markets to reorganize their internal organization. Especially the complex and not standardized procurement process holds high cost reduction potential. To exploit this potential, suppliers need to understand the purchasing routines of their buyers. Hence, a rising number of supplying firms consider e-procurement solutions to foster and to optimize the direct link to their buyers. The central question of this contribution concerns the role of e-procurement in procurement processes of industrial buyers and reports the results of a respective survey study among 100 construction firms in Austria. The survey study focuses on the adoption rate of e-procurement solutions as well as the used functions and software solutions. Furthermore, benefits and barriers of buyers in the construction industry for using e-procurement systems are highlighted. The findings show that e-procurement is not frequently adopted in the construction industry and that the potential for cost reduction is not exploited to the full. Article history: Received (10.12.2013); Revised (23.02.2014); Accepted (10.03.2014)